2021
DOI: 10.1002/aur.2663
|View full text |Cite
|
Sign up to set email alerts
|

Features that best define the heterogeneity and homogeneity of autism in preschool‐age children: A multisite case–control analysis replicated across two independent samples

Abstract: The heterogeneous nature of children with symptoms of autism spectrum disorder (ASD) makes it difficult to identify risk factors and effective treatment options. We sought to identify behavioral and developmental features that best define the heterogeneity and homogeneity in 2-5-year-old children classified with ASD and subthreshold ASD characteristics. Children were enrolled in a multisite casecontrol study of ASD. Detailed behavioral and developmental data were gathered by maternal telephone interview, paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Introduction: Heterogeneity thwarts autism explanatory power: Can transdiagnostic behavioral endophenotypes help? patterns, comorbidities, and biomarkers (3)(4)(5)(6)(7). Casanova et al (8) asserted that, "The diagnostic boundaries of the behavioral phenotype that define ASD are fairly broad due to the large variability that is observed in symptom types, onset, and severity.…”
Section: Abstract Autism Heterogeneity Diagnosis Paradigm Dsm- Subgro...mentioning
confidence: 99%
See 3 more Smart Citations
“…Introduction: Heterogeneity thwarts autism explanatory power: Can transdiagnostic behavioral endophenotypes help? patterns, comorbidities, and biomarkers (3)(4)(5)(6)(7). Casanova et al (8) asserted that, "The diagnostic boundaries of the behavioral phenotype that define ASD are fairly broad due to the large variability that is observed in symptom types, onset, and severity.…”
Section: Abstract Autism Heterogeneity Diagnosis Paradigm Dsm- Subgro...mentioning
confidence: 99%
“…The efforts for reducing autism heterogeneity-creating prototypical autism, excluding moderate-to-severe autism symptoms, creating subgroups, and increasing sample sizes-have not yet been effective in reducing heterogeneity. Thus, heterogeneity remains an unresolved problem (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Moreover, as discussed previously, establishing the unitary DSM-5 ASD diagnosis has not reduced autism heterogeneity.…”
Section: Summary Of E Orts To Reduce Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings might be underscored by a recent systematic review (Canu et al, 2021) on non‐social behavioral indicators of ASD in infant siblings, which suggested that non‐social signs appear much ahead of the full manifestation of social impairments. Moreover, these non‐social behavioral markers could be specific for ASD, rather than a general marker of global developmental delay (DD) (Canu et al, 2021; Wiggins et al, 2021). Furthermore, behaviors outside of the social‐communication domain, such as atypical sensory hyper‐and hypo‐reactivity, dysregulation, sensory‐motor repetitions, motor challenges and atypical visual attention may be important to study for their developmental precedence (Baranek et al, 2018; Robertson & Baron‐Cohen, 2017; Sacrey et al, 2014; Thye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%